Socio-cultural aspects: the key to sustainable WASH behaviour? : a case study in southwest Uganda - Strand, Annie (SLU/Dept. of Urban and Rural Development, 2010)

(untitled)
Despite investments of $15 billion in the WASH-sector the millennium development goal on sanitation will not be met. This is partially because of lack of sufficient knowledge about the socio-cultural environments of the projects. Socio-cultural aspects have not been investigated sufficiently, if at all, in most project designs, and this leads to behaviour change that is not sustainable.